2010
DOI: 10.1002/hep.23921
|View full text |Cite
|
Sign up to set email alerts
|

Biliverdin inhibits hepatitis C virus nonstructural 3/4A protease activity: Mechanism for the antiviral effects of heme oxygenase?

Abstract: Induction of heme oxygenase-1 (HO-1) inhibits hepatitis C virus (HCV) replication. Of the products of the reaction catalyzed by HO-1, iron has been shown to inhibit HCV ribonucleic acid (RNA) polymerase, but little is known about the antiviral activity of biliverdin (BV). Herein, we report that BV inhibits viral replication and viral protein expression in a dose-dependent manner in replicons and cells harboring the infectious J6/JFH construct. Using the SensoLyte 620 HCV Protease Assay with a wide wavelength e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
106
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 72 publications
5
106
0
Order By: Relevance
“…This clearly shows the antiviral role of HO-1 in hepatocytes (Zhu et al 2008). Our lab and others investigated the role of HO-1 products; carbon monoxide, iron and biliverdin on HCV replication (Hou et al 2009;Lehmann et al 2010;Zhu et al 2010). Interestingly, biliverdin seems to contribute to the antiviral activity of HO-1.…”
Section: Heme Oxygenase-1 and Viral Replicationmentioning
confidence: 73%
See 1 more Smart Citation
“…This clearly shows the antiviral role of HO-1 in hepatocytes (Zhu et al 2008). Our lab and others investigated the role of HO-1 products; carbon monoxide, iron and biliverdin on HCV replication (Hou et al 2009;Lehmann et al 2010;Zhu et al 2010). Interestingly, biliverdin seems to contribute to the antiviral activity of HO-1.…”
Section: Heme Oxygenase-1 and Viral Replicationmentioning
confidence: 73%
“…Biliverdin was shown to interfere with HCV replication, and specifically, by inhibiting HCV NS3/4A protease. Moreover, biliverdin exerts its effect by inducing the expression of antiviral interferons, such as interferon α2 and α17 (Lehmann et al 2010;Zhu et al 2010). It is clear that HO-1 products have inhibitory effect on HCV.…”
Section: Heme Oxygenase-1 and Viral Replicationmentioning
confidence: 99%
“…Induction or overexpression of HO-1 also suppresses hepatitis C virus (HCV) replication and protects hepatocytes from oxidative damage (14). In addition, the HO-1 product biliverdin inhibits HCV replication by increasing the antiviral interferon response (51,52). Our previous work showed that HO-1 induction using different concentrations of CoPP greatly decreases both recombinant PRRSV and wild-type PRRSV replication in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…2 Likewise, Zhu et al recently demonstrated that BV has potent antiviral activity against HCV, with inhibitory action over HCV NS3/4A protease. 3 Iron has also been shown to inhibit HCV replication by preventing divalent caption binding to RdRp.…”
mentioning
confidence: 99%
“…In vitro studies have reported that BR and BV show antiviral activity against HIV, the herpes virus, and HCV. 3 More specifically, the antiviral action against HCV is due to both recombinant and endogenous NS3/4A protease from replicon microsomes being inhibited by BR and BV.…”
mentioning
confidence: 99%